The problems of learning english vocabulary in harapan senior high school - Krisnayanti, Ni Putu Ari; Winarta, I.B. Gde Nova (Journal of Language and Applied Linguistics, 2021)
The aim of this study is to find out the problems in learning English Vocabulary especially in the eleventh-grade students of Harapan Senior High School Denpasar. In this study, the writer had 70 students of 11 social 2 and 11 social 3 at eleventh-grade students in Harapan Senior High School Denpasar. The writer gave a test to the participants. Since this study has purpose to know the students’ problem in learning vocabulary, the writer also interviewed 3 students who got lower score than other students to get rich description of the problems. The eleventh-grade students still have many difficulties in vocabulary learning. The categorization of the student problem is based on vocabulary learning aspects, such as pronunciation, spelling, word meaning and word use. The average score that the students got in pronunciation is 81,43%, in spelling is 59,71%, in word meaning is 71,02%, and in word use the students got 73,33%. So, the students still have problems in vocabulary. Furthermore, the problem can be caused by many factors, such as: hard to memorize many words, their motivation, or lack of experience in language learning.